Crambe oil (Crambe abyssinica) preheated in diesel engine - Martins Bomfati , Bruna; Colonhese Delalibera, Hevandro; Riyuiti Higashibara , Leandro; Alberti Gomes, Jaime; Weirich Neto, Pedro Henrique (Latin American Journal of Energy Research, 2023)
Studies indicate derivatives of vegetable and animal oils as substitutes for Diesel (PD). However, the use of these as fuel has changed or strategies to reduce its adoption. Therefore, an experiment was carried out using crambe oil (CR) preheated to 100 °C in a Diesel engine cycle (PD). CR and PD are accommodated, every 15 hours of operation, in four absorption regimes, up to 100 hours of work. The regimes were, 1100 rpm without load, 1800 rpm without load, 1800 rpm with 51% and 66% of nominal power. Note that the consumption of CR was higher than that of PD, with a more pronounced difference in regimes under load, with a greater loss of relative power being observed in the use of CR when changing the load. There was no difference between the two fuels for thermal efficiency. For the cooling fluid and lubricant, higher temperatures were observed for the CR, but the temperature of the exhaust gases and the lubricant pressure were higher for the PD. At the end of the test, there was an increase in pressure and opening pressure of the injector, and the injector elements showed carbonization, difficult to remove, wear and signs of overheating. There was no evidence of oil degradation.
Keywords: biofuel, vegetable oil, fuel consumption, bioenergy, sustainable development